Enhancing Urban Thermal Environment in Public Open Spaces through ENVI-met Simulation and WSUD principle - Saffanah, Yannah; Syafii, Nedyomukti Imam (Jurnal Planologi, 2025)
ABSTRACTGlobal climate change and the Urban Heat Island (UHI) phenomenon have significantly impacted outdoor thermal comfort in urban environments, particularly in equatorial tropical cities such as Pontianak, Indonesia. This study evaluates the effectiveness of integrating Water Sensitive Urban Design (WSUD) principles into the design of public open spaces, using the case of the Pangsuma Sports Complex in Pontianak. The research employs urban microclimate simulation through ENVI-met software to assess key parameters such as air temperature, humidity, and wind speed. The results demonstrate that WSUD-oriented urban design—incorporating water bodies, dense vegetation, and permeable materials—can effectively improve thermal comfort. Simulations indicate a reduction in ambient temperature from 25°C to 24°C, an increase in wind speed from 0.8 m/s to 1.35 m/s, and a decrease in humidity from 72.94% to 68.37%, achieving optimal thermal comfort based on national standards. These findings affirm WSUD as a responsive urban design strategy that addresses microclimatic discomfort while enhancing ecological sustainability, water resilience, and public well-being in water-based cities. This research underscores the critical role of climate-responsive urban design in shaping livable, adaptive, and sustainable public spaces for tropical urban futures.Keywords: Water-Sensitive Urban Design, Urban Microclimate, ENVI-met; Thermal comfort, Urban Heat Island Mitigation. ABSTRAKPerubahan iklim global dan fenomena Urban Heat Island (UHI) telah mempengaruhi kenyamanan termal di ruang terbuka kota, terutama di wilayah tropis seperti Kota Pontianak. Penelitian ini mengevaluasi efektivitas penerapan desain ruang terbuka publik berbasis prinsip Water Sensitive Urban Design (WSUD) dalam meningkatkan kenyamanan termal kawasan Gelanggang Olahraga Pangsuma, Pontianak. Metode yang digunakan meliputi pemodelan dan simulasi menggunakan perangkat lunak ENVI-met untuk menganalisis parameter iklim mikro seperti suhu udara, kelembapan, dan kecepatan angin. Hasil penelitian menunjukkan bahwa penerapan elemen WSUD seperti badan air, vegetasi tinggi, dan material permeabel secara signifikan menurunkan suhu dari 25°C menjadi 24°C, meningkatkan kecepatan angin dari 0,8 m/s menjadi 1,35 m/s, serta menurunkan kelembapan udara dari 72,94% menjadi 68,37%. Kondisi ini menciptakan kenyamanan termal optimal berdasarkan standar nasional. Konsep WSUD terbukti tidak hanya sebagai solusi terhadap ketidaknyamanan termal, tetapi juga sebagai strategi adaptif terhadap perubahan iklim yang mendukung keberlanjutan lingkungan dan meningkatkan kualitas hidup masyarakat kota berbasis perairan. Penelitian ini merekomendasikan integrasi WSUD dalam perancangan ruang publik sebagai bagian dari strategi pembangunan kota berkelanjutan di iklim tropis.Kata kunci: Water Sensitive Urban Design, Iklim Mikro Perkotaan, ENVI-Met, Kenyamanan Termal, Mitigasi Pulau Panas Perkotaan